ILD-GAP Combined with the Charlson Comorbidity Index Score (ILD-GAPC) as a Prognostic Prediction Model in Patients with Interstitial Lung Disease. (8th February 2023) - Fujii, Hiroaki; Hara, Yu; Saigusa, Yusuke; Tagami, Yoichi; Murohashi, Kota; Nagasawa, Ryo; Aoki, Ayako; Izawa, Ami; Seki, Kenichi; Watanabe, Keisuke; Horita, Nobuyuki; Kobayashi, Nobuaki; et al.
Abstract : Background . The ILD-GAP scoring system has been widely used to predict the prognosis of patients with interstitial lung disease (ILD). The ability of the ILD-GAP scoring system combined with the Charlson Comorbidity Index score (CCIS) (ILD-GAPC) to predict ILD prognosis was investigated. Methods . In ILD patients, including idiopathic pulmonary fibrosis (IPF), idiopathic nonspecific interstitial pneumonia (iNSIP), collagen vascular disease-related interstitial pneumonia (CVD-IP), chronic hypersensitivity pneumonitis (CHP), and unclassifiable ILD (UC-ILD), treated between April 2013 and April 2017, the relationships between baseline clinical parameters, including age, sex, CCIS, ILD diagnosis, pulmonary function test results, and disease outcomes, were retrospectively assessed, and the ability to predict prognosis was compared between the ILD-GAP and ILD-GAPC models, respectively. Results . A total of 185 patients (mean age, 71.9 years), all of whom underwent pulmonary function testing, including percentage predicted diffusion capacity for carbon monoxide, were assessed. ILD diagnosis consisted of IPF in 57 cases, iNSIP and CVD-IP in 117 cases, CHP in 6 cases, and UC-ILD in 5 cases. The ILD-GAPC provided a greater area under the receiver operating characteristic curve (0.758) for predicting 3-year ILD-related events than the ILD-GAP (0.721). In addition, log-rank tests showed that the Kaplan−Meier curves differed significantly among low, middle, and high ILD-GAPC scores (P < 0.001 ), unlike ILD-GAP scores (P = 0.083 ). Conclusions . The ILD-GAPC model could provide more accurate information for predicting prognosis in patients with ILD than the ILD-GAP model.